IN THE DESERTS - Murray, Laura K., 1989- (Mankato, Minnesota : Creative Education and Creative Paperbacks, 2019)
From shortest to tallest and biggest to smallest, this ecosystem investigation uses varying degrees of comparison to take a closer look at the relationships of desert flora, fauna, and landforms.
t Long roots -- t In the deserts. Word review -- Read more & websites -- Index.
Includes index
Keywords: Desert animals -- Juvenile literature; Body size -- Juvenile literature; Deserts -- Environmental conditions -- Juvenile literature; Juvenile works; Picture books